A Transformation Method for Delta Partial Difference Equations on Discrete Time Scale. (10th July 2020) - Haider, Syed Sabyel; Rehman, Mujeeb Ur; Abdeljawad, Thabet
Abstract : The aim of this study is to develop a transform method for discrete calculus. We define the double Laplace transforms in a discrete setting and discuss its existence and uniqueness with some of its important properties. The delta double Laplace transforms have been presented for integer and noninteger order partial differences. For illustration, the delta double Laplace transforms are applied to solve partial difference equation.